Penerapan model pembelajaran kooperatif Tipe student team achievement division Untukmeningkatkan hasil belajar ips Siswa kelas v sd negeri 001 teluk makmur Kota dumai - Donald Alfara Dwi Putra Donald Alfara Dwi Putra; Hendri Marhadi Hendri Marhadi; Gustimal witri Gustimal witri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : This study was motivated by the low IPS student learning outcomes, with the average grade 68.47. While the completeness criteria Maximum value (KKM) IPS is 75th Among ISWA totaling 23 people, only 7 students who achieve ketuntasn classical KKM with 30.43%. This research is Classroom Action Research (CAR) conducted aims to improve learning outcomes IPS Elementary School fifth grade students 001 Prosperous Bay Dumai by implementing cooperative learning model-Student Team Achievement Division (STAD). Formulation of the problem: Is the application of cooperative learning model-Student Team Achievement Division (STAD) can improve learning outcomes IPS Elementary School fifth grade students 001 Prosperous Bay City Dumai.penelitian is held from 9 April 2014 until April 25 2014dengan 2 cycles. Subjects were fifth grade students of SD Negeri 01 Gulf Makmur Dumai by the number of students sebanyak23 the students as a source of data. Data collection instrument in this thesis is the activity sheet and sheet activities siswaserta teacher learning outcomes. This thesis presents the results of the study were obtained daily before action replay value with an average of 68.47, an increase in the first cycle with the average being 78.47. In the second cycle increased by an average of 81.30. Observation activities of teachers in the learning process in the first cycle the first meeting and the second meeting 50% increase to 62.5%. Cycle II first meeting and the second meeting 66.66% 83.33% increase to the observation of the activities of students in the first cycle the first meeting and the second meeting of 58.33% increased to 66.66%. The first meeting of the second cycle and 75% for the second meeting had risen to 83.33%. The results of the study in class V Prosperous Bay Elementary School 001 Dumai prove that the application of cooperative model-type Student Team Achievement Division (STAD) can improve learning outcomes IPS Elementary School fifth grade students Dumai 001 ProsperousBay. Keywords: Cooperative Learning Model of type Student Team-Achievement Division (STAD).